Role of Ocrelizumab in modulating gene and microRNA expression in multiple sclerosis - Bruna De Felice; Elisabetta Signoriello; Concetta Montanino; Giuseppe Romano; Deborah Archetto; Elisabetta Maida; Martina Marciano; Simona Bonavita; Giacomo Lus; Federica Farinella; Cinzia Coppola (Non-coding RNA Research)
Multiple sclerosis is an autoimmune neurodegenerative disease and one of the most significant challenges in modern neurology, impacting approximately 2.8 million people globally. As a multifactorial condition, susceptibility to MS can result from a combination of genetic and environmental factors. Current treatment strategies aim to prevent acute attacks, slow disease progression, and alleviate symptoms. Ocrelizumab, a monoclonal antibody targeting CD20, has demonstrated efficacy in clinical trials by reducing both disease activity and frequency of relapses.Given the recent approval of this treatment, we investigated whether Ocrelizumab alters the expression of key miRNAs and genes involved in neuroinflammation, such as let-7a-5p, miR-14a-5p, miR-21a-5p, miR-338-3p, IL-1, IL-6, NEAT1, NEFL, NESTIN, SLC16A10 and TNF-alpha, by comparing their expression in patients’ blood before and after one year of treatment with Ocrelizumab. Additionally, we explored potential inverse correlations and direct or indirect interactions among the genes and miRNAs that showed significant changes in expression. Lastly, we conducted a pathway analysis to understand the overall effects potentially exerted by the drug.Results revealed a significant decrease in the expression of TNF-alpha, SLC16A10, NEFL and IL-6, and an increase in let-7a-5p expression. There was an inverse correlation between let-7a-5p and the four genes, while the genes positively correlated with each other, suggesting let-7a-5p as a common modulator. These findings indicate that further investigation is needed to determine if the drug directly upregulates let-7a-5p, thereby downregulating the four genes, or if these expression changes are an indication of an overall reduction in inflammation.